Cost effectiveness analysis of zinc supplementation in acute diarrhea in children - Gregorio, Germana V.
Theses--((Master of Science in Epidemiology-Clinical Epidemiology) UPCM
Background: Zinc supplementation has been shown to cause a reduction in the duration of diarrhea. However, the decision to incorporate it is the diarrhea control program of the country will be based on the cost of supplementation against the reduction in the number of days with diarrhea. Objective: To determine whether zinc with oral rehydration solution (ORS) is more effective as compared to ORS alone in the treatment of acute childhood diarrhea. Study Design: Cost-effectiveness analysis (CEA). Method: Participants of an on-going randomized trial of zinc + ORS versus ORS alone in the treatment of acute diarrhea consulting at the University of the Philippines-Philippine General Hospital (UP-PGH) emergency room and at the Paco and San Andres local health centers were recruited for this study. Included were children aged between 2 to 59 months with a history of diarrhea of <7 days duration and no dehydration. Excluded were those with current intake of zinc supplement and antibiotics, presence of systematic medical illness and severe malnutrition. The cost was considered from the society's perspective. The cost values were derived from the UP-PGH cost figures. Effectiveness measures were: per day of diarrhea averted and per case of diarrhea averted <4 days from consult. A comparison of the direct medical and nonmedical costs and indirect cost was done. The incremental cost-effectiveness ration (ICER) between the two groups was calculated. A cost-effectiveness plane was constructed. Results: All continuous data were expressed as mean #SD. Sixty patients in the zinc + ORS and 57 in the ORS group were recruited. The mean duration od diarrhea was shorter (2.98 # 0.92 vs 3.67 # 1.63 days, p=0.0009) and the mean total cost of treatment (P 1500.83#311.08 vs P 1587.66# P 1587.66#499.71, p_0.26) was 5% cheaper in the zinc + ORS compared to the ORS group. A higher mean drug cost was a higher mean indirect medical cost was seen in the ORS group (P 992.28#439.77 vs P 835.25 #257.32, p=0.02. The incremental cost effectiveness ration (ICER) showed that with the use of zinc + ORS, the society saves P 127.50 (95% CI: P-221.19 to 226.33) per day of diarrhea averted and P7.92 (95% CI: P-16.48 to 0.625) per case of diarrhea averted <4 days from consult. the cost effectiveness plane showed that the zinc + ORS group is less costly and more effective as compared to the ORS group. Conclusion: Zinc with ORS is more cost effective as compared to ORS alone in the treatment of acute childhood diarrhea.
Keywords: Diarrhea; Zinc